THE EFFECT OF COMPETENCE AND WORK DISCIPLINE ON REWARDS WITH WORK INFRASTRUCTURE AS A MODERATING VARIABLE AT PT PLN (PERSERO) SERVICE IMPLEMENTATION UNIT RANTAUPRAPAT CUSTOMERS - Hendra Gunawan Nainggolan; Kiki Farida Ferine (CV. Radja Publika, 2025)
This study aims to analyze the influence of Competence and Work Discipline on Rewards with Work Infrastructure as a moderating variable at PT PLN (Persero) Rantauprapat Customer Service Implementation Unit. This study uses a quantitative approach with the Partial Least Square Structural Equation Modeling (PLS-SEM) analysis method. The number of respondents in this study was 86 people. The results showed that Competence (coefficient = 0.388; T-statistic = 3.266; P-values ​​= 0.001) and Work Discipline (coefficient = 0.276; T-statistic = 2.307; P-values ​​= 0.011) had a positive and significant effect on Rewards. Work Infrastructure also had a positive and significant effect on Rewards (coefficient = 0.362; T-statistic = 3.274; P-values ​​= 0.001). However, the moderation effect test shows that the interaction between Competence and Work Infrastructure (coefficient = -0.031; T-statistic = 0.235; P-values ​​= 0.407), as well as the interaction between Work Discipline and Work Infrastructure (coefficient = 0.112; T-statistic = 0.900; P-values ​​= 0.184), do not significantly influence Rewards. Thus, employee Rewards are more directly influenced by competence, discipline, and the availability of work infrastructure, compared to the moderating effect of work infrastructure.